LncRNA Expression Signatures in Periodontitis Revealed by Microarray: The Potential Role of lncRNAs in Periodontitis Pathogenesis. Issue 4 (April 2015) - Zou, Yaguang; Li, Chun; Shu, Fangpeng; Tian, Zhihui; Xu, Wenan; Xu, Huiyong; Tian, Hua; Shi, Rong; Mao, Xiangming
ABSTRACT Periodontitis, a common chronic inflammatory disease of the periodontium, is caused by dental plaque formation induced by microorganisms. Recent studies have demonstrated that lncRNAs play a critical role in the regulation of gene expression and in the pathogenesis of diseases. To demonstrate that periodontitis is associated with lncRNAs, microarray analysis was used to detect differently expressed lncRNAs in chronic periodontitis and adjacent normal tissues. The results of some differently expressed lncRNAs were further confirmed using real‐time PCR. A total of 8925 differentially expressed lncRNAs were detected, including 4313 upregulated lncRNAs and 4612 downregulated lncRNAs. Further lncRNA subgroup analysis showed there were 589 enhancer‐like lncRNAs, 238 homeobox (HOX) cluster lncRNAs, and 1218 Rinn's lincRNAs, of which 656 lincRNAs were upregulated and 562 lincRNAs were downregulated. Therefore, we confirmed that lncRNAs were differently expressed in chronic periodontitis tissues compared with adjacent normal tissues, indicating that lncRNAs may exert partial or key roles in periodontitis pathogenesis and development. Taken together, this study may provide potential targets for future treatment of periodontitis and novel diagnostic biomarkers for periodontitis. J. Cell. Biochem. 116: 640–647, 2015. © 2014 Wiley Periodicals, Inc.